Rapid recovery of invertebrate communities after ecological restoration of boreal mires. Issue 5 (17th June 2015) - Noreika, Norbertas; Kotiaho, Janne S.; Penttinen, Jouni; Punttila, Pekka; Vuori, Anna; Pajunen, Timo; Autio, Olli; Loukola, Olli J.; Kotze, D. Johan
Abstract : Mire degradation due to drainage for forestry results in the loss of mire specialist species. To halt the loss in biodiversity, ecological restoration is needed and already implemented. However, a major challenge in ecological restoration is whether actions taken have the desired outcome. Key abiotic and biotic conditions for the successful restoration of invertebrate communities can be identified by testing the "Field of Dreams" hypothesis, which postulates that if a habitat is successfully restored, species will return. This study was conducted in nine boreal mires located in Eastern Finland, 1–3 years after restoration. Parts of each mire were drained for forestry during the 1960s and 1970s, and restored in 2003–2006. Two 250 m transects were established in each of three treatments (pristine, drained, restored) per mire. We used pitfall trapping to sample carabid beetles and spiders, sweep netting to sample micromoths and crane flies and counts along the transects to sample macromoths. Vegetation cover, water table level, and climatic variables were measured along all transects. Mire specialist species and invertebrate communities responded positively to restoration and negatively to drainage, whereas generalists showed varied responses. In addition, mire specialists were associated with high cover of Sphagnum mosses and with low numbers of tall trees (>3 m). Therefore, to successfully restore populations and communities of mire specialist invertebrates, maintaining environmental conditions that favor the growth of Sphagnum mosses, rewetting the sites and removing larger trees are necessary measures.